Berakhirnya Mitos Dikotomi Santri-Abangan - Abdul Mughits (Millah: Journal of Religious Studies, 2004)
Santri and abangan are two cultural terminologies which have been customary known by Java society since Islam  had entered in this island. The expression to each of  them is point toward to different meaning, santri is term to express the Java Muslim that is faithful to the Islamic religion commands and abangan is term to express the Jawa Muslim that not obey them. The latest terminology really expresses the stereotype and negative cultural values. Each of  them had made the limits in social and cultural discourse, especially in their political movement since the rising of  nationalism (1908) to the general elections (1955). Their social behaviors and cultural characters have made a dichotomy between themselves. This convergention has been witnessed by Javanese, especially, since the absorption between Islamic society and New Orde government so that convergention can be reason to end the santri and abangan  dichotomy.